1995
DOI: 10.21236/ada360259
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Causes Platelet Dysfunction and Induces Fibrinolysis Before the Institution of Cardiopulmonary Bypass

Abstract: Reproduction in whole or in part is permitted for any purpose of Cw the United States Government. *n Distribution of this report is unlimited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…24 A previous study from our laboratory has documented that heparin produced a platelet dysfunction and fibrinolysis in patients before cardiopulmonary bypass surgery. 25 In another study from our laboratory infusion of heparin into the baboon induced fibrinolytic activity, 100 units per kg of heparin produced a heparin level of 7.8 units per mL and a plasmin level of 72.7 units per liter 50 minutes following the infusion into baboons. 26 Antifibrinolytic agents like aprotonin and epsilon aminocaproic acid are used to inhibit the fibrinolytic activity associated with cardiopulmonary bypass surgical procedures.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…24 A previous study from our laboratory has documented that heparin produced a platelet dysfunction and fibrinolysis in patients before cardiopulmonary bypass surgery. 25 In another study from our laboratory infusion of heparin into the baboon induced fibrinolytic activity, 100 units per kg of heparin produced a heparin level of 7.8 units per mL and a plasmin level of 72.7 units per liter 50 minutes following the infusion into baboons. 26 Antifibrinolytic agents like aprotonin and epsilon aminocaproic acid are used to inhibit the fibrinolytic activity associated with cardiopulmonary bypass surgical procedures.…”
Section: Discussionmentioning
confidence: 93%
“…Treatment of the plasma with urokinase simulated the fibrinolytic activity produced by heparin and by the clotting and lysis of shed blood. 25,26 Treatment of plasma to inhibit the fibrinolytic activity of urokinase with the antifibrinolytic agent aprotonin simulated the quality of shed blood collected during and following cardiopulmonary bypass surgical procedures. 27,28 The volume of treated plasma infused equivalent to 15% of the blood volume simulated the volume of plasma reinfused with nonwashed shed blood that was not associated with a bleeding disorder in patients.…”
mentioning
confidence: 99%
“…The conventional perfusion strategy, which employs non-thromboresistant bypass circuits and high-dose heparin used in the vast majority of the cardiopulmonary bypass based cardiac surgeries, incites strong inflammatory responses [5,11,12], hemolytic turbulence, and significant activation of the coagulation and fibrinolytic systems during and after the procedure [4,[13][14][15]. Multiple measures were taken clinically to alleviate these potentially harmful responses, using pharmacologic agents [16][17][18][19], mechanical means such as leukocytes filters [20], various compounds and methods for surface coatings [21], or eliminating the foreign surfaces by performing ''off-pump'' coronary bypass grafting [21].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Our laboratory also has used the baboon to study the effects of hypothermia on hemostasis before we conducted the experiments in normal volunteers and patients. [4][5][6][7][8][9][10] We have found that data obtained from baboon studies are similar to those seen in studies of normal volunteers and believe that human studies can be reduced by using the baboon in specific areas of research. The following experiments were performed to evaluate the effects of various disinfection treatments on the survival and function of red blood cells and platelets.…”
Section: The Effect Of Disinfection On Viability and Functionmentioning
confidence: 92%